BARRIERS TO INITIATE INSULIN THERAPY FOR PATIENTS WITH TYPE 2 DIABETES MELLITUS AT SANGLAH HOSPITAL DENPASAR - Kresnasari, Ni Luh Putri; Budhiarta, A.A.Gde; Saraswati, Made Ratna (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana, 2013)
Diabetes mellitus is a growing global health concern. Types 2 diabetes mellitus poses a major global health threat, especially in the developing country of the world. Most patients will eventually require insulin therapy in order to reach their good glycemic control. But many patients types 2 diabetes mellitus feel some barriers to initiate insulin therapy. This is quantitative descriptive study which take place at interna policlinic Sanglah Hospital from 6-29 January 2011 with total population 94 patient type 2 diabetes mellitus with using insulin therapy and their age > 40 years. Patients interviewed about barriers to initiate insulin therapy. From 94 patients who take insulin therapy, get 38 (40,42%) have some barriers. The reasons is fear of needle (19 or 20,21%), fear of pain from insulin injections (16 or 17,02%), fear of weight gain (7 or 7,45%), fear of hypoglicemia or other complications (4 or 4,25%), insulin is too expensive (5 atau 5,32%), not sure of the way using insulin (6 or 6,38%), afraid of negatif conception from the others (4 or 4,25%), and other barriers (1 or 1,06%). This study, we hope physicians can identified the barriers before give the insulin therapy. Growing relationship between doctor and patient with of good communication and give a logic and easy explaination about insulin therapy.
Keywords: type 2 diabetes melitus, therapy insulin, barriers, communication.